Study on the mechanism of action of effective monomeric, berberine of Xianglian Pill in inhibiting human colon cancer cells based on fatty acid synthase target - Li, Shi-ying; Li, Yun; Wu, Zhong-hua; Zhou, Zhang-jie; Li, Cun-ya; Wu, Ting-ting; Fu, Shu-juan; Wang, Zhi-ying; Zhong, Zhi-xian; Zhong, Yi (Journal of Traditional and Complementary Medicine, 2023)
Background and aim: Xianglian Wan (XLW) as a classic prescription of traditional Chinese medicine protects digestive function; however, few studies have investigated its anti-colorectal cancer effects. This study verified that the effective monomer berberine of XLW plays an antitumo r role by regulating the acetyl-CoA carboxylase (ACC)/fatty acid synthase (FASN) lipid metabolism-related signaling pathway. Experimental procedure: The connection between XLW and FASN was identified through literature mining, bioinformatics and structural biology. In vivo experiments verified the rationality of the antitumor effect of berberine by regulating the ACC/FASN pathway, and in vitro experiments verified the regulatory relationship between berberine and FASN. Results and conclusion: The most frequent Chinese medicine component in XLW was Coptis chinensis. Berberine, the active ingredient of XLW, has a FASN binding site. FASN expression is higher in tumor tissues than in normal tissues. FASN is related to colorectal adenocarcinoma occurrence and patient survival time. Experiments showed that XLW, berberine and orlistat (FASN inhibitor) can cooperate with palmitic acid (PA) to inhibit tumors in mice. Berberine can downregulate FASN and ACC expression in tumor tissues and inhibit the increase in acetyl-CoA, the intermediate product of exogenous PA intake. The mechanism by which berberine inhibits colon cancer cell proliferation by lowering lipids is related to its downregulation of FASN protein expression. The ACC/FASN signaling pathway is a critical pathway through which berberine, the effective monomer of XLW, plays an antitumor role in colon cancer.